The investigation of the actual work of metal suspension bridge for a pipeline through the Dnieper river with a span of 720 m - Tarnopolskyi, O. O.; Rotmistrovskyi, M. M.; Kazakevych, M. I. (Science and Transport Progress, 2008)
The results of more than 30-year monitoring and investigations of the real work state of exceptional suspended bridge steel structures made in 1978 are presented in the paper. The major problems and difficulties discovered in the process of the structure exploitation as well as authors’ design approaches for their elimination are given here.